Analisis Potensi Komoditas Unggulan Nenas di Tapanuli Utara dengan Metode Location Quotient (LQ) dan Peluang Produk Olahan untuk Ekspor - Erni Susilawati Purba; Jelita Maria Christine Samosir; Josua, Josua Adrio Sihombing; Kristin Margaretha Simarmata; Simeon Adrian Simatupang; Fahmi Ashari S. Sihaloho (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the potential of superior commodities in North Tapanuli Regency, especially pineapple commodities, using the Location Quotient (LQ) method. North Tapanuli Regency is known to have abundant agricultural resources, but not all of them have been optimized for export purposes. In this study, secondary data in the form of GRDP in 2024 from BPS was used as the basis for calculating LQ to identify the base sector. The results of the study showed that of several agricultural sub-sectors, pineapple fruit commodities had the highest LQ value of 7.89, which indicated that pineapple has a comparative advantage and is very potential to be developed as an export product. To support the development of this commodity, a SWOT analysis was conducted on two main processed products, namely pineapple dodol and pineapple chips. This analysis shows that pineapple is not only superior in terms of production quantity, but also has great potential to be developed into high value-added products. These findings provide an important contribution to the strategy for developing local commodities that are export-oriented and support sustainable regional economic development.